Marketing Efficiency in Cut Roses: A Comparative Study of Organised Vis-A-Vis Unorganised Markets - Vidhyashree, H.S.; Santhosha, K. M., Ganeshagouda I. Patil, C. G. Yadava; Gagana, M. D.; Ramappa, K. B; Srinivasalu G. B.; Raghavendra (Archives of Current Research International, 2024)
The present study is mainly about the comparative analysis of marketing efficiency of cut roses under organised and unorganised markets. For the present study, the primary data was collected from the Krishna Raja Market, Bengaluru an unorganised market, whereas the International Flower Auction Centre, Bengaluru (IFAB) is an organised market. Data collected from 40 market intermediaries in each market structure and total intermediaries were to be 80. Forty rose vendors are randomly selected to gather marketing constraints in organised market. In the study area, three major marketing channels were observed for cut rose marketing in unorganised market structure: Channel I: Producer – Wholesaler – Retailer – Consumer; Channel II: Producer – Retailer – Consumer; and Channel III: Producer– Commission agent– Retailer – Consumer, whereas in the organised market, two marketing channels were prominent, i.e., Channel I: Producer – IFAB – Wholesaler – Retailer – Consumer and Channel II: Producer – IFAB – Retailer – Consumer. Marketing efficiency was estimated using the Acharya and Agarwal methodology. In this analysis, direct marketing channel was found to be the most efficient for unorganised and organised markets. Marketing constraints were analysed using Rank Based Quotient (RBQ) technique. Quality standards and the lack of price information were the most important problems for the farmers while marketing the flowers in organised markets rather than unorganised markets. Hence, policymakers should provide producers with the required facilities and impart proper knowledge about quality standards to farmers, leading to more income for producers.